The functional roles of the three copper sites associated with the methionine-rich insert in the multicopper oxidase CueO from E. coli1. Issue 5 (13th May 2015) - Cortes, Laura; Wedd, Anthony G.; Xiao, Zhiguang
<x xml:space="preserve">Abstract</x> The methionine-rich insert in the multicopper oxidase CueO from E. coli accommodates three copper sites that play distinct but related roles in Cu(i) extraction and oxidation and that induce robust cuprous oxidase activity under physiologically relevant conditions.